Yoga mat with double-sided anti-skid textures and preparation method of yoga mat

By using a mesh cloth with a larger mesh and a high viscosity slurry, combined with the coating and foaming process, the problem of not being able to obtain double-sided anti-slip texture yoga mats in the prior art through one-piece molding is solved, and the effect of simplifying the process and reducing costs is achieved.

CN119499610APending Publication Date: 2025-02-25GUANGDONG YUANHUA NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411461952.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art cannot obtain yoga mats with double-sided anti-slip marks through a one-piece molding process, resulting in complex processes and increased costs.

Method used

A mesh cloth with a larger mesh hole and a high viscosity slurry is used to form a double-sided anti-slip textured yoga mat through the coating and foaming process. The mesh width or diameter of the mesh cloth is 2-4mm, the width of the mesh is not less than the length/width/diameter of the mesh, and the viscosity of the slurry is greater than 1*105mpa.s.

Benefits of technology

A yoga mat with double-sided anti-slip texture is achieved through one-time scraping and foaming, which simplifies process steps, reduces costs, and improves anti-slip effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499610A_ABST
    Figure CN119499610A_ABST
Patent Text Reader

Abstract

The invention discloses a yoga mat with double-sided anti-skid textures and a preparation method thereof, and relates to the technical field of yoga mats, the yoga mat comprises a mat body and mesh cloth embedded in the mat body, the mesh cloth comprises grids and meshes, the width of the grids is not smaller than the length / width / diameter of the meshes, the length / width / diameter of the meshes is 2-4 mm, and the mesh cloth is made of non-woven fabric. The meshes in the adjacent rows are staggered; the viscosity of slurry for preparing the pad body is greater than 1 * 10 < 5 > mpa.s. The yoga mat with double-sided anti-skid textures can be obtained by adopting the mesh cloth with larger meshes and the slurry with higher viscosity through scraping and foaming; wherein the meshes and the grids of the mesh cloth can enable the slurry to permeate to the other surface of the mesh cloth and are not adhered to each other, and meanwhile, the high-viscosity slurry is adopted, so that the slurry can permeate through the meshes but is not leveled and can be attached to the meshes without falling off, and after foaming, the slurry at the corresponding meshes can form bulges on the upper surface and the lower surface of the mesh cloth; therefore, the effect of double-sided anti-skid textures is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of yoga mats, and in particular to a yoga mat with double-sided anti-slip textures and a preparation method thereof. Background Art

[0002] Yoga mats are widely used in yoga exercises or as outdoor mats. In order to make them anti-slip, anti-slip textures are usually set on their lower surfaces. For example, when applying slurry, the slurry is infiltrated into the bottom surface of the mesh by the action of a scraper, and then an anti-slip texture is formed on the bottom of the mat body. However, due to the viscosity of the slurry and the mesh, this method can only form an anti-slip texture on the bottom surface of the mesh, and the surface to be scraped can only form a plane to obtain a double-sided anti-slip texture. The prior art usually obtains an anti-slip texture on the surface without texture by embossing after the mat body is foamed and formed, which leads to a complicated process and increased costs. In addition, the prior art also obtains a double-sided anti-slip texture by compounding two layers of mat bodies, which also makes the process steps more complicated, and the thickness of the mat body after compounding increases, resulting in increased costs. It can be seen that the prior art cannot obtain a yoga mat with double-sided anti-slip textures through a one-time molding process.

[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a yoga mat with a double-sided anti-slip texture and a preparation method thereof, aiming to solve the problem in the prior art that a yoga mat with a double-sided anti-slip texture cannot be obtained by one-time molding.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A yoga mat with a double-sided anti-slip texture, comprising a mat body and a mesh embedded in the mat body, wherein the mesh comprises a grid and mesh holes, the width of the grid is not less than the length / width / diameter of the mesh hole, the length / width / diameter of the mesh hole is 2-4 mm, and the mesh holes in adjacent rows are staggered; the viscosity of the slurry for preparing the mat body is greater than 1*10 5 mpa.s.

[0007] In the yoga mat with double-sided anti-slip texture, the mesh holes are rectangular mesh holes.

[0008] In the yoga mat with double-sided anti-slip texture, the width of the grid is 2 to 5 mm.

[0009] In the yoga mat with double-sided anti-slip texture, the raw material components for preparing the slurry include, by weight: 30 to 70 parts of a first PVC paste resin powder, 30 to 50 parts of a second PVC paste resin powder, 80 to 90 parts of a plasticizer, 2 to 2.5 parts of a stabilizer, 30 to 40 parts of a filler, 8 to 12 parts of a foaming agent, 20 to 30 parts of talc, and 0.5 to 1.0 parts of a tackifier.

[0010] In the yoga mat with double-sided anti-slip texture, the particle size of the talcum powder is 1000-1500 meshes.

[0011] In the yoga mat with double-sided anti-slip texture, the polymerization degree of the first PVC paste resin powder is 800-950, and the polymerization degree of the second PVC paste resin powder is 1100-1200.

[0012] The yoga mat with double-sided anti-slip texture according to claim 4, characterized in that the plasticizer is selected from diisononyl phthalate or diisooctyl cyclohexane-1,2-dicarboxylate.

[0013] A method for preparing a yoga mat, wherein the method is used to prepare a yoga mat with a double-sided anti-slip texture as claimed in any one of claims 1 to 7, the method comprising the following preparation steps: taking each raw material component according to a proportion, stirring and mixing until the viscosity thereof is greater than 1*10 5 mpa.s to obtain slurry; coating the slurry on the mesh and leveling it with upper and lower scrapers; foaming, and cooling to obtain a yoga mat with double-sided anti-slip texture.

[0014] Beneficial effects:

[0015] The present invention provides a yoga mat with double-sided anti-skid textures. The yoga mat adopts a mesh with larger mesh holes and a slurry with higher viscosity. After coating and foaming, the yoga mat with double-sided anti-skid textures can be obtained. The mesh hole width or diameter of the mesh is 2-4 mm, so that the slurry can penetrate through the mesh holes to the other side of the mesh cloth. At the same time, by making the width of the mesh not less than the width of the mesh cloth, the slurry passing through the mesh does not adhere to each other, so that the slurry passing through the mesh can form anti-skid protrusions on the upper surface of the mesh cloth after foaming. Furthermore, by adopting a high-viscosity slurry, it can penetrate through the mesh holes without being leveled, and can adhere to the mesh holes without losing the slurry. Then, after foaming, the slurry at the corresponding mesh holes can form protrusions on the upper and lower surfaces of the mesh cloth, thereby having the effect of double-sided anti-skid textures. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A physical picture of the yoga mat with double-sided anti-slip texture provided by the present invention (the left side is the lower surface of the mesh, and the right side is the upper surface of the mesh).

[0017] Figure 2 Schematic diagram of the structure of the mesh.

[0018] Markings in the accompanying drawings: 1-mesh, 2-grid, 3-mesh. DETAILED DESCRIPTION

[0019] The present invention provides a yoga mat with a double-sided anti-slip texture and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] See also Figure 1 The present invention provides a yoga mat with double-sided anti-skid texture, wherein the upper surface and the lower surface of the yoga mat are both formed with anti-skid texture, and the double-sided anti-skid texture is not obtained by embossing or composite double-layer pad body, but is obtained by one-time foaming molding. The yoga mat comprises a mat body and a mesh 1 embedded in the mat body, wherein the mesh 1 is used to support the slurry during the preparation process, and the mesh is provided with a grid 2 and a mesh hole 3 so that the width of the grid 2 is not less than the length / width / diameter of the mesh hole 3, and the length / width / diameter of the mesh hole 3 is 2-4 mm, and the mesh holes 3 located in adjacent rows are misaligned. The mesh with a special structure can make the slurry attached thereto pass through the mesh holes and enter the upper surface of the mesh after being scraped, and then form foaming protrusions on the upper and lower surfaces of the mesh after foaming, thereby improving the anti-slip effect; in addition, in order to achieve the effect of having an anti-slip texture on both sides, it is necessary to prevent the slurry passing through the mesh holes from falling off and not being leveled, so the viscosity of the slurry scraped on the mesh needs to be greater than 1*10 5 mpa.s, the slurry of this viscosity can pass through the mesh under the action of the scraper, but it will not flow flat after passing through. After the scraper is withdrawn, it will partially move downward under the action of gravity, but the slurry will not fall off, so that after foaming, independent foaming protrusions can be formed on the upper and lower surfaces of the mesh.

[0021] In this embodiment, a mesh cloth with a special structure is adopted, which has mesh holes that allow the slurry to pass through, and at the same time, a grid of appropriate width is set to avoid the slurry from sticking after passing through the mesh holes, so as to maintain independence of each other, and at the same time, by adjusting the viscosity of the slurry, part of the slurry is allowed to pass through the mesh holes by scraping but not leveled, and the slurry is hung on the mesh holes without falling off, so that after foaming, the slurry at the corresponding mesh position can form foaming protrusions on the upper and lower surfaces of the mesh cloth, and these foaming protrusions do not stick to each other, and can form anti-slip textures on the upper and lower surfaces of the mat body, which has a double-sided anti-slip effect; since the yoga mat does not require embossing and double-layer composite to obtain a double-sided anti-slip texture, it has a better anti-slip effect and is relatively low in cost.

[0022] In the aforementioned yoga mat, the structure of the mesh will affect the formation of the anti-slip texture and the shape of the texture, such as the shape and size of the mesh, the area ratio of the mesh to the mat body, the width of the grid, etc. The shape of the mesh is different, and the texture formed by the slurry passing through the mesh will also be different. For example, a rectangular mesh can form an elliptical protrusion on the bottom surface of the mat body, while a square or circular mesh can form a square or circular protrusion on the bottom surface of the mat body. However, when the mesh area is the same, the square and circular meshes have higher requirements for the viscosity of the slurry, which will increase the difficulty of scraping. Therefore, the preferred mesh shape is rectangular, which can form an elliptical protrusion, has a better anti-slip effect and a good ornamental effect.

[0023] Secondly, since the size of the mesh will affect the amount of slurry that passes through the mesh and the situation of slurry hanging, when the mesh size is too large, slurry is prone to fall off, and the viscosity of the slurry needs to be increased. However, when the viscosity of the slurry is too high, the slurry is difficult to apply and scrape, the difficulty of slurry penetration increases, and even the thickness is uneven; and when the mesh size is too small, the amount of slurry penetration is too small, resulting in unclear anti-slip texture and insufficient anti-slip effect. In this regard, in a preferred embodiment, the mesh is a rectangular mesh, and the aspect ratio of the rectangular mesh is 3:2, and the width of the rectangular mesh is 2 to 4 mm, which has a better slurry penetration effect, and can make the slurry hang without falling when the viscosity of the slurry is small, and can form anti-slip textures on both sides of the pad after foaming.

[0024] In addition to the aforementioned effects on the anti-skid texture on both sides of the pad body, the width of the grid, that is, the spacing between the meshes, will also affect the formation of the anti-skid texture. When the spacing between the meshes is small, the slurry passing through the meshes is prone to sticking to each other or leveling, resulting in the inability to form an anti-skid texture on the surface of the mesh cloth; when the spacing between the meshes is large, the number of meshes per unit area will be reduced, resulting in a smaller number of foamed protrusions, resulting in a poor anti-skid effect. In this regard, in a preferred embodiment, the spacing between the meshes is not less than 3mm, and increases with the increase in the size of the mesh. Preferably, the width of the grid is 1mm larger than the width of the mesh, and the area of ​​the mesh in the pad body accounts for 1 / 3 to 1 / 2, which can form a better double-sided anti-skid texture with a good anti-skid effect.

[0025] In order to obtain a slurry with a higher viscosity to meet the needs of coating slurry during preparation, in a preferred embodiment, the raw material components for preparing the slurry include, by weight: 30-70 parts of the first PVC paste resin powder, 30-50 parts of the second PVC paste resin powder, 80-90 parts of plasticizer, 2-2.5 parts of stabilizer, 30-40 parts of filler, 8-12 parts of foaming agent, 20-30 parts of talcum powder, and 0.5-1.0 parts of tackifier. The raw materials with this composition ratio can obtain a viscosity greater than 1*10 5mpa.s slurry, and due to the addition of talcum powder and tackifier, the slurry has a high viscosity and good fluidity when applied. In particular, the added talcum powder can increase the viscosity of the slurry in static state to ensure that the slurry does not fall off, but it can also reduce the shear force of the slurry, so that the slurry can penetrate the mesh and enter the upper surface of the mesh when applied, making the thickness of the pad more uniform.

[0026] In a preferred embodiment, the particle size of the talcum powder is 1000-1500 meshes. The talcum powder with this particle size has a more obvious effect on the viscosity and shear force of the slurry and has a better effect.

[0027] In a preferred embodiment, the polymerization degree of the first PVC paste resin powder is 800-950, and the polymerization degree of the second PVC paste resin powder is 1100-1200. By using the two PVC paste resin powders with different polymerization degrees together, the viscosity of the slurry can be better adjusted.

[0028] In another preferred embodiment, the plasticizer is selected from diisononyl phthalate or diisooctyl cyclohexane-1,2-dicarboxylate, which has a good thickening effect and will not precipitate during use, which is more environmentally friendly; preferably, when the plasticizer is diisooctyl cyclohexane-1,2-dicarboxylate, its synergistic effect with the second PVC paste resin powder can better improve the toughness of the pad body.

[0029] It should be noted that the stabilizer, foaming agent and filler are all conventional materials and will not be described in detail herein.

[0030] The second aspect of the present invention also provides a method for preparing a yoga mat with a double-sided anti-slip texture, the method comprising the following preparation steps: taking each raw material component according to a proportion, stirring and mixing until the viscosity thereof is greater than 1*10 5 mpa.s to obtain a slurry; coating the slurry on a mesh and leveling it with a scraper; and after foaming and cooling, obtaining a yoga mat with a double-sided anti-slip texture.

[0031] In the preparation method, after slurry coating, the excess slurry is scraped off by the action of a scraper to obtain a pad body of a specific thickness. On the other hand, the slurry located on the bottom surface of the mesh is passed through the mesh holes into the upper surface of the mesh cloth by the action of the scraper, and the slurry at the grid will be scraped off, and only part of it will be attached to the bottom surface of the grid; the slurry at the corresponding mesh hole, due to its high viscosity, can still hang in the mesh hole, and part of it is located above the mesh hole, and because of the high viscosity, the slurry of adjacent mesh holes will not flow and adhere; and then after foaming, the slurry in the corresponding mesh hole will form foaming protrusions above and below the mesh hole, and the slurry adhered to the grid is less, so no large foaming protrusions will be formed, so anti-skid textures are formed on the upper and lower surfaces of the pad body. The preparation method has simple steps, and a yoga mat with double-sided anti-skid texture can be obtained by one-time scraping and foaming. Compared with the existing method of obtaining double-sided anti-skid textures by multi-layer composite or embossing, the preparation method has simpler steps, lower cost, and can better control the thickness of the pad body.

[0032] To further illustrate a yoga mat with double-sided anti-slip texture and a preparation method thereof provided by the present invention, the following embodiments are provided.

[0033] Example 1

[0034] A yoga mat with double-sided anti-slip texture is prepared by the following method:

[0035] Take the following raw materials according to the ratio: 50 parts of the first PVC paste resin powder (average degree of polymerization is 850), 40 parts of the second PVC paste resin powder (average degree of polymerization is 1200), 80 parts of diisononyl phthalate, 2.2 parts of stabilizer, 50 parts of filler, 10 parts of foaming agent, 25 parts of talcum powder (average particle size is 1500 mesh), 0.8 parts of tackifier; stir and mix the raw materials, and measure the viscosity greater than 1*10 5 mpa.s, to obtain a slurry; coating the slurry on a mesh cloth having rectangular meshes, the size of the rectangular meshes being 4 mm long and 3 mm wide, and the width of the grid being 5 mm; flattening the slurry with upper and lower scrapers, and then foaming and cooling to obtain a yoga mat with a double-sided anti-slip texture.

[0036] Example 2

[0037] A yoga mat with double-sided anti-slip texture is prepared by the following method:

[0038] Take the following raw materials according to the proportion: 30 parts of the first PVC paste resin powder (average degree of polymerization is 800), 50 parts of the second PVC paste resin powder (average degree of polymerization is 1200), 90 parts of dioctyl cyclohexane-1,2-dicarboxylate, 2 parts of stabilizer, 30 parts of filler, 8 parts of foaming agent, 30 parts of talcum powder (average particle size is 1000 mesh), 0.5 parts of tackifier; stir and mix the raw materials, and measure the viscosity greater than 1*10 5 mpa.s, to obtain a slurry; coating the slurry on a mesh cloth having rectangular mesh holes, the size of the rectangular mesh holes being 3 mm in length and 2 mm in width, and the width of the grid being 3 mm; flattening the slurry with upper and lower scrapers, and then foaming and cooling to obtain a yoga mat with a double-sided anti-slip texture.

[0039] Example 3

[0040] A yoga mat with double-sided anti-slip texture is prepared by the following method:

[0041] Take the following raw materials according to the proportion: 70 parts of the first PVC paste resin powder (average degree of polymerization is 950), 30 parts of the second PVC paste resin powder (average degree of polymerization is 1100), 80 parts of diisooctyl cyclohexane-1,2-dicarboxylate, 2.5 parts of stabilizer, 40 parts of filler, 12 parts of foaming agent, 20 parts of talcum powder (average particle size is 1500 mesh), 1.0 part of tackifier; stir and mix the raw materials, and measure the viscosity greater than 1*10 5 mpa.s, a slurry is obtained; the slurry is coated on a mesh cloth, the mesh cloth has a square mesh, a side length of 4 mm, and a mesh width of 5 mm; the slurry is flattened by upper and lower scrapers, and then foamed and cooled to obtain a yoga mat with a double-sided anti-slip texture.

[0042] Comparative Example 1

[0043] A yoga mat, the preparation method of which is basically the same as that of Example 1, except that no talcum powder and tackifier are added, and the slurry viscosity is 4.2X10 4 mpa.s.

[0044] Comparative Example 2

[0045] A yoga mat, the preparation method of which is basically the same as that of Example 1, except that no talcum powder is added, and the slurry viscosity is 9.3X10 4 mpa.s.

[0046] Comparative Example 3

[0047] A yoga mat, the preparation method of which is basically the same as that of Example 1, except that the mesh cloth used is a mesh cloth with warp and weft threads crisscrossed vertically and horizontally, and the distance between adjacent warp threads and the distance between adjacent weft threads are both 2 mm, which is equivalent to the side length of the formed square mesh being 2 mm.

[0048] Comparative Example 4

[0049] A yoga mat, the preparation method of which is basically the same as that of Example 1, except that the mesh holes of the mesh cloth used are square mesh holes, and the size of the square mesh holes is 8 mm.

[0050] Comparative Example 5

[0051] A yoga mat, the preparation method of which is basically the same as that of Example 1, except that the particle size of the talcum powder is 300 mesh, the slurry viscosity is 8.02X10 4 mpa.s.

[0052] It should be noted that, in Examples 1-3 and Comparative Examples 1-5, the slurry is applied to the same thickness, and the thickness of the cushion body after foaming in Examples 1-3 is about 6 mm.

[0053] Performance Testing

[0054] According to the standard ASTM-F609, the static friction coefficient of the front and back of the pads of Examples 1-3 and Comparative Examples 1-5 was tested; 10 points were randomly selected on the 1X2 pad to measure the thickness (avoiding points at gaps or holes), and the difference between the highest and lowest thickness values ​​among the 10 points was taken as the thickness difference; appearance test: by shining light on one side of the pad, observe whether the other side of the pad has light transmission, and at the same time observe whether both sides have anti-slip textures. All test results are shown in Table 1.

[0055] Table 1. Performance test results

[0056]

[0057] It can be seen from Table 1 that the yoga mats obtained in Examples 1-3 have double-sided anti-slip textures, and the static friction coefficients on the front and back sides are both relatively large, with good anti-slip effects, and the thickness difference is almost negligible, with no light transmission phenomenon.

[0058] The yoga mat prepared in Comparative Example 1 also has anti-slip textures on both sides, and the static friction coefficients of the front and back sides exceed 0.88. However, due to the low viscosity of the slurry, there is leakage of slurry during application, and holes are formed on the mat body after molding. These holes are easy to hide dirt and grime, and are prone to mold over time, making them difficult to be accepted by consumers.

[0059] The anti-skid properties of both sides of Comparative Example 2 are good, but the thickness difference is large, mainly because the addition of talcum powder causes the high viscosity slurry to easily cause uneven thickness when applied, which ultimately makes the pad body uneven in thickness.

[0060] Comparative Example 3 uses a mesh cloth with alternating warp and weft, which can only form a single-sided anti-skid texture, resulting in a small static friction coefficient on the front side and poor anti-skid effect.

[0061] In Comparative Example 4, since the mesh size of the mesh cloth is too large, even if the slurry viscosity is relatively high, there will still be slurry leakage, resulting in holes in the mat body, which cannot meet the needs of consumers.

[0062] In Comparative Example 5, since the talcum powder used has a large particle size, it cannot play a viscosity-increasing role, resulting in leakage of the slurry. In addition, since the talcum powder has a large particle size, it cannot reduce the shear force of the slurry, resulting in uneven thickness during application, and ultimately uneven thickness of the pad body.

[0063] In summary, the yoga mat with double-sided anti-skid texture of the present invention is made of special mesh and slurry with high viscosity, and the single-layer mat body has double-sided anti-skid texture, and the anti-skid effect is very good. The preparation method can form double-sided anti-skid texture by only one slurry coating and foaming, and the steps are simple and easy to implement.

[0064] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.

Claims

1. A yoga mat with double-sided anti-slip texture, characterized in that: It comprises a pad body and a mesh cloth embedded in the pad body, the mesh cloth comprises a grid and mesh holes, the width of the grid is not less than the length / width / diameter of the mesh hole, the length / width / diameter of the mesh hole is 2-4 mm, and the mesh holes in adjacent rows are staggered; The viscosity of the slurry used to prepare the pad is greater than 1*10 5 mpa.s.

2. The yoga mat with double-sided anti-slip texture according to claim 1, characterized in that: The mesh is a rectangular mesh.

3. The yoga mat with double-sided anti-slip texture according to claim 2, characterized in that: The width of the grid is 2 to 5 mm.

4. The yoga mat with double-sided anti-slip texture according to claim 1, characterized in that: The raw material components for preparing the slurry include, by weight: 30 to 70 parts of a first PVC paste resin powder, 30 to 50 parts of a second PVC paste resin powder, 80 to 90 parts of a plasticizer, 2 to 2.5 parts of a stabilizer, 30 to 40 parts of a filler, 8 to 12 parts of a foaming agent, 20 to 30 parts of talc, and 0.5 to 1.0 parts of a tackifier.

5. The yoga mat with double-sided anti-slip texture according to claim 4, characterized in that: The particle size of the talcum powder is 1000-1500 meshes.

6. The yoga mat with double-sided anti-slip texture according to claim 4, characterized in that: The polymerization degree of the first PVC paste resin powder is 800-950, and the polymerization degree of the second PVC paste resin powder is 1100-1200.

7. The yoga mat with double-sided anti-slip texture according to claim 4, characterized in that: The plasticizer is selected from diisononyl phthalate or diisooctyl cyclohexane-1,2-dicarboxylate.

8. A method for preparing a yoga mat, characterized in that: For preparing a yoga mat with a double-sided anti-slip texture as claimed in any one of claims 1 to 7, the method comprises the following preparation steps: taking each raw material component according to a proportion, stirring and mixing until the viscosity thereof is greater than 1*10 5 mpa.s to obtain slurry; coating the slurry on the mesh and leveling it with upper and lower scrapers; foaming, and cooling to obtain a yoga mat with double-sided anti-slip texture.

Citation Information

Patent Citations

  • Heat-preservation foaming material for tent and preparation method of heat-preservation foaming material for tent

    CN104494257A

  • Massage cushion and preparation method thereof

    CN105860317A

  • Yoga ground mat

    CN107268279A

  • Wear-resistant and scratch-resistant yoga mat and preparation method thereof

    CN115814328A

  • T-shaped mesh for non-slip mat base materials

    CN201850380U